Importance Destination Loyalty: The Case Monumen Tugu Pahlawan in Surabaya, East Java - Mustika, Hindah; Jamil, Mochamad; Ximenes, Mateus (KINERJA, 2024)
The focus of the research is to examine and analyze the factors of the importance of destination loyalty in historical places. It can be said that historical places have their uniqueness or characteristics as an identity and value that must be preserved. Method: This research uses a quantitative method where SEM-PLS is used to test and analyze the collected data in the form of respondents' answers in the questionnaire. The number of respondents was 210, who had characteristics of educational background, age, gender, and social media used so that this could describe the level of respondents' understanding of knowledge and love of historical places. Results showed that the three antecedents are tourist satisfaction, patriotism, and gender, which motivate someone to intend and re-visit a monument and influence destination loyalty. It can be clearly illustrated that respondents have a strong emotional bond with the historical value of destination loyalty. Novelty: gender has an important meaning and can be a moderating variable. Originality: historical value in the form of the results of the struggle of Surabaya youth against the colonialists, which is then realized in a destination.